National Security as a Corporate Social Responsibility: Critical Infrastructure Resilience - Ridley, Gail (2011)
This article argues for an extension to the scope of corporate social responsibility (CSR) research to include a contemporary issue of importance to national and global security, critical infrastructure resilience. Rather than extending the multiple perspectives on CSR, this study aimed to identify a method of recognising CSR-related issues, before applying it to two dissimilar case studies on critical infrastructure resilience. One case study was of an international telecommunications company based in the US while the other was of the railway network in Britain during a period of privatisation. The method used was derived from Okoye’s (J Bus Ethics 89(4):613–627, 2009) common reference core for CSR. Both case studies satisfied all the criteria sought which points to critical infrastructure resilience as being an emerging CSR issue. Because ongoing change characterises CSR, the method may have application for identifying future new CSR strands. As the findings suggest that some aspects of national and global security are CSR-related phenomena, the study demonstrates how CSR research may be significant at a societal, national and global level. Implications of the study include a broadening of the value and reach of contributions from CSR researchers and practitioners.
Keywords: National security; Microsoft Corporation; essentially contested concepts; critical infrastructure resilience; Corporate Social Responsibility; Case study; British railway industry